Medicinal Plants as Biocultural Resistance: Epistemic Justice and Intergenerational Dialogue in Rural Colombia - Bohórquez Acosta, Irlena Esther; Rueda Arciniegas, Diana Milena (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
Situated in Piñalito, Meta—a region deeply impacted by the Colombian armed conflict and currently facing the challenges of neoliberal agricultural expansion—this article explores how kindergarten children engage with medicinal plants as a practice of world making. Moving beyond a mere pedagogical strategy to teach scientific concepts, this participatory action research involves children, families, and teachers as co-researchers in a horizontal dialogue. We argue that recovering ancestral knowledge is an act of epistemic justice that counters the erasure of local traditions and the commercialization of seeds. Through intergenerational encounters and the exploration of biocultural memory, children do not just learn about plants; they construct identities rooted in the care of life and territorial resistance. The findings suggest that early childhood education can be a pivotal space for decolonizing knowledge and strengthening community bonds against the lasting scars of violence and displacement.